Melioidosis diagnostic workshop, 2013. - Hoffmaster, A; AuCoin, D; Baccam, P; Baggett, H; Baird, R; Bhengsri, S; Blaney, D; Brett, P; Brooks, T; Brown, K; Chantratita, N; Cheng, A; et al. (Centers for Disease Control and Prevention, 2015)
Melioidosis is a severe disease that can be difficult to diagnose because of its diverse clinical manifestations and a lack of adequate diagnostic capabilities for suspected cases. There is broad interest in improving detection and diagnosis of this disease not only in melioidosis-endemic regions but also outside these regions because melioidosis may be underreported and poses a potential bioterrorism challenge for public health authorities. Therefore, a workshop of academic, government, and private sector personnel from around the world was convened to discuss the current state of melioidosis diagnostics, diagnostic needs, and future directions.